Bioassays: A Rapid and Label‐free SERS Detection Method for Biomarkers in Clinical Biofluids (Small 24/2014). Issue 24 (December 2014) - Kong, Kien Voon; Leong, Weng Kee; Lam, Zhiyong; Gong, Tianxun; Goh, Douglas; Lau, Weber Kam On; Olivo, Malini
<x xml:space="preserve">Abstract</x> W. K. Leong, M. Olivo, and co‐workers show the use of a metal carbonyl‐functionalized, nanostructured substrate in a rapid and simple assay for the detection of a potential biomarker for bladder cancer in clinical urine samples. On page 5030, changes in the carbonyl stretching vibrations, which lie in a spectral window free from interference from biomolecules, are monitored via SERS. This method is superior to current techniques, which typically involve multiple reagents and skilled handling, thus allowing SERS‐based biomarker assays for clinical diagnosis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>